(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
The Melamchi Water Supply Project (MWSP) is designed to minimize the shortage of drinking water in the Kathmandu valley. Although the project was supposed to be completed by 2008, due to various problems, it is still difficult to forecast the exact date of completion. This paper quantifies the downstream effects of diverting water from the Melamchi (Stage-I), Yangri (Stage-II) and Larke (Stage-III) rivers under current as well as future climate scenarios. The Soil Water Assessment Tool (SWAT) was used in the analysis. Result shows that in the Stage-I water transfer plan, average inflow reduction in the immediate downstream sub-basin in the dry and wet seasons are 36% and 7% respectively, where as in Stage-II the inflow reductions are 38% for the dry season and 8% for the wet season. In Stage-III, inflow reductions are 38% in the dry season and 7% in the wet season. The impact of the water transfer schemes on various changes in water management within the Melamchi River irrigation command area was also tested. BUDGET (soil, water and salt balance) model was used to quantify crop water requirement of Melamchi River command area when the irrigated area is increased and the cropping pattern is changed. Simulation results of crop water requirement in intensive water use conditions show that present Melamchi River command area can be increased by 2.2 times under current climate projection, whereas the area can be increased 1.4 times in 2030s and by 2.0 times in 2050s. DOI: http://dx.doi.org/10.3126/hn.v11i1.7199 Hydro Nepal Special Issue: Conference Proceedings 2012 pp.23-29